Empathie: Hilfe oder Hindernis bei aktuellen Integrationsaufgaben und dem Umgang mit Radikalisierung? - Meier, Rebecca

Rezension des Buches "Sonderschullehrerausbildung im Nationalsozialismus" (2014) von Dagmar Hänsel - Kottmann, Brigitte (Behindertenpädagogik)

Die Nutzung institutioneller Lerngelegenheiten und die Entwicklung bildungswissenschaftlichen Wissens angehender Lehrkräfte. - Christina, Watson; Seifert, Andreas; Schaper, Niclas (Zeitschrift für Erziehungswissenschaften)

Food justice, common heritage and the oceans: Resource narratives in the context of the Third United Nations Conference on the Law of the Sea - Sackel, Johanna (International Journal of Maritime History)
The United Nations Conference on the Law of the Sea was an arena in which global resource equity was negotiated in a process that extended beyond the governmental actors who took centre stage. But our perceptions of the role of an increasingly civil society in framing national decision-making processes during the 1970s – for instance, through trade associations or nongovernmental organizations – is blurred. Both civil society and economic actors crafted similar policies, though for different purposes: some – with regard to the north–south divide – focused on the conservation of the ocean’s resources over the long term, whereas others were more concerned with short-term economic benefits. This article asks which arguments legitimized property and usage rights, and which resource narratives were used. By taking into account the charged relationship of local–national–global reaches, it also examines perceptions and management of resources in the context of resource equity on a global scale.
Keywords: Transportation; History

Unterrichtsplanung im Fach Geschichte – Modellierung und Erfassung geschichtsdidaktischen Planungswissens von Lehramtsstudierenden - Wolf, Jörgen; Seiffert, Joana; Seifert, Andreas; Rothland, Martin; Brauch, Nicola (Die Unterrichtsplanung: Ein in Vergessenheit geratener Kompetenzbereich?! Status und Perspektiven aus der Sicht der empirischen Forschung.)

Constructing a Language From Scratch: Combining Bottom–Up and Top–Down Learning Processes in a Computational Model of Language Acquisition - Gaspers, Judith; Cimiano, Philipp; Rohlfing, Katharina; Wrede, Britta (IEEE Transactions on Cognitive and Developmental Systems)

Taking Up an Active Role: Emerging Participation in Early Mother–Infant Interaction during Peekaboo Routines - Nomikou, Iris; Leonardi, Giuseppe; Radkowska, Alicja; Rączaszek-Leonardi, Joanna; Rohlfing, Katharina (Frontiers in Psychology)

Verbs in mothers’ input to six-month-olds: Synchrony between presentation, meaning, and actions Is related to later verb acquisition. - Nomikou, Iris; Koke, Monique; Rohlfing, Katharina (Brain Sciences)

“Can you teach me?” – Children teaching new words to a robot in a book reading scenario. - Grimminger, Angela; Rohlfing, Katharina (Proceedings of the 6th International Workshop on Child Computer Interaction (WOCCI 2017))

In Infants' Hands: Identification of Preverbal Infants at Risk for Primary Language Delay - Lüke, Carina; Grimminger, Angela; Rohlfing, Katharina; Liszkowski, Ulf; Ritterfeld, Ute (CHILD DEVELOPMENT)
Early identification of primary language delay is crucial to implement effective prevention programs. Available screening instruments are based on parents' reports and have only insufficient predictive validity. This study employed observational measures of preverbal infants' gestural communication to test its predictive validity for identifying later language delays. Pointing behavior of fifty-nine 12-month-old infants was analyzed and related to their language skills 1 year later. Results confirm predictive validity of preverbal communication for language skills with the hand shape of pointing being superior compared to the underlying motives for pointing (imperative vs. declarative). Twelve-month-olds who pointed only with their open hand but never with their index finger were at risk for primary language delay at 2 years of age.

Studienerfolg als der Erwerb bildungswissenschaftlichen Wissens vs. Studienerfolg als Veränderung der Kompetenzselbsteinschätzungen: Entwicklungen im Praxissemester. - Seifert, Andreas (Gemeinsame Tagung der Fachgruppen Entwicklungspsychologie und Pädagogische Psychologie)

Analytical competence of teachers: modelling and validating a core construct. - Scholl, Daniel; Seifert, Andreas; Krepf, Matthias; Plöger, Wilfried (Congress “New International Perspectives on Future Teacher’s Professional Compe-tencies”)

Neue Herausforderungen für Zentren für Lehrerbildung. - Schaper, NIclas; Festner, Dagmar; Seifert, Andreas; Watson, Christina; Hilligus, Annegret Helen (10. Bundeskongress der Zentren für Lehrerbildung.)

Test-Development to Assess Future History Teacher’s PCK. - Brauch, Nicola; Wolf, Jörgen; Seiffert, Joana; Seifert, Andreas; Rothland, Martin (17th Biennial EARLI Conference)

In Infants' Hands: Identification of Preverbal Infants at Risk for Primary Language Delay - Lüke, Carina; Grimminger, Angela; Rohlfing, Katharina; Liszkowski, Ulf; Ritterfeld, Ute (CHILD DEVELOPMENT)
Early identification of primary language delay is crucial to implement effective prevention programs. Available screening instruments are based on parents' reports and have only insufficient predictive validity. This study employed observational measures of preverbal infants' gestural communication to test its predictive validity for identifying later language delays. Pointing behavior of fifty-nine 12-month-old infants was analyzed and related to their language skills 1 year later. Results confirm predictive validity of preverbal communication for language skills with the hand shape of pointing being superior compared to the underlying motives for pointing (imperative vs. declarative). Twelve-month-olds who pointed only with their open hand but never with their index finger were at risk for primary language delay at 2 years of age.

Gestische und sprachliche Kommunikation von 12—16 Monate alten Kindern und ihren Bezugspersonen in wiederkehrenden, semi-naturalistischen Interaktionen und individuelle Unterschiede in der späteren Sprachentwicklung - Grimminger, Angela

„That is why I believe I can do it” - Prediction of Self-Efficacy Towards Inclusive Education in Austrian and German Prospective Teachers. Individual Paper Presentation. 2017 IACESA (International Association for Cognitive Education in Southern Africa) Conference - Schwab, Susanne; Hellmich, Frank; Görel, Gamze

Leseleistungen von Grundschulkindern im Zusammenhang mit dem Feedback ihrer Lehrkräfte im Leseunterricht – Befunde aus einer Mehrebenenanalyse. Posterpräsentation auf der 5. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Hoya, Fabian Karl; Hellmich, Frank

Under which conditions do primary school teachers cooperate in inclusive education? Single Paper. 17th Biennial EARLI (European Association for Research on Learning and Instruction) - Hellmich, Frank; Schwab, Susanne; Hoya, Fabian Karl; Görel, Gamze

Prerequisites of Primary School Students` Attitudes Towards Peers with Social or Emotional Disorders. Single Paper. 17th Biennial EARLI (European Association for Research on Learning and Instruction) - Löper, Marwin Felix; Hellmich, Frank

Inklusiver Unterricht in der Grundschule

Paderborner Qualitätsstern zur Einschätzung der Kooperation im Übergang Kita - Grundschule (Online-Ressource, Bezug über https://blogs.uni-paderborn.de/paderborner-qualitaetsstern/) - Höke, Julia; Büker, Petra; Bührmann, Thorsten
Weitere Angaben: Paderborn: Universität Paderborn Download unter upb.de/paderborner-qualitaetsstern-kita-gs (URL am 8.10.2020 nicht mehr aktuell, Weiterleitung eingerichtet)

Familien- und Elternbildung stärken - Faas, Stefan; Landhäußer, Sandra; Treptow, Rainer
Vor dem Hintergrund eines anhaltenden Diskurses um veränderte Anforderungen an Familien und die Notwendigkeit einer stärkeren öffentlichen Verantwortung für das Aufwachsen von Kindern richten die Autoren dieses Buches den Blick auf den Bereich der Eltern- und Familienbildung. Im Mittelpunkt stehen verschiedene Konzepte und Entwicklungen, die auf eine Stärkung dieses Handlungsfelds zielen, insbesondere im Sinne einer Erhöhung der Akzeptanz und Nachfrage von Eltern. Dabei werden Potentiale und Grenzen ausgewählter Konzepte auf der Grundlage aktueller empirischer Untersuchungen diskutiert.
Keywords: Sozialwissenschaften; Pädagogik; Politik/Verwaltung; Soziologie; Sozialpädagogik

BMBF-Tagung: Bildungsforschung 2020: Interdisziplinäre und interinstitutionelle Po-tenziale eines Veranstaltungsformats. - Schütz, Julia; Seifert, Andreas (Der Pädagogische Blick)

Sprachliche Sozialgeschichte des Nationalsozialismus – Themen und Zugänge - Schubert, Katrin; Krüger, Carolin (Bericht zur Tagung am Institut für Deutsche Sprache (IDS) in Mannheim, 7. und 8. April 2017. In ZGL, Jg. 45 Heft 3)

Reference as an Interactive Achievement: Sequential and Longitudinal Analyses of Labeling Interactions in Shared Book Reading and Free Play - Heller, Vivian; Rohlfing, Katharina (Frontiers in Psychology)

Benefits of repeated book readings in children with SLI - Rohlfing, Katharina; Ceurremans, Josefa; Horst, Jessica S. (Communication Disorders Quarterly)

Diagnostik des vorsprachlichen Kommunikationsverhaltens: Pilotstudie zur Konstruktvalidität eines neuen Elternfragebogens (Komm!-Bogen). - Müller, Christina; Grimminger, Angela; Caroli, Brigitte; Rohlfing, Katharina (Frühförderung Interdisziplinär)

Development of pointing gestures in children with typical and delayed language acquisition. - Lüke, Carina; Ritterfeld, Ute; Grimminger, Angela; Liszkowski, Ulf; Rohlfing, Katharina (Journal of Speech, Language, and Hearing Research)

An Interactive View on the Development of Deictic Pointing in Infancy. - Rohlfing, Katharina; Grimminger, Angela; Lüke, Carina (Frontiers in Psychology)

Kompetenzselbsteinschätzungen und bildungswissenschaftliches Wissen im Lehramtsstudium – Zeigen sich Unterschiede zwischen einem Orientierungspraktikum und dem Praxissemester? - Festner, Dagmar; Gröschner, Alexander; Seifert, Andreas (2. Internationalen Kongress „Lernen in der Praxis.“)

Learning to Practice (LtP): Ermittlung der Kompetenzentwicklung im Praxissemester – Pädagogisches Wissen und Kompetenzeinschätzungen. - Seifert, Andreas; Schaper, Niclas; König, JOhannes (Vortrag auf dem NRW-Netzwerktreffen Lehrerbildung 2017)

Veränderungen des bildungswissenschaftlichen Wissens und der subjektiven Kompetenzeinschätzungen von Studierenden im Praxissemester. - Seifert, Andreas; Schaper, Niclas (2. Internationalen Kongress „Lernen in der Praxis.“)

Die Befragungen im bildungswissenschaftlichen Studium an der Universität Paderborn: Ansatz, Ergebnisse, Implikationen, Verbesserungsmöglichkeiten. - Seifert, Andreas (Forschungskolloquium der Psychologie)

Hören – Sprechen – Lesen – Schreiben. Band 1: Basale Sprachfähigkeiten. DaM – DaZ – DaF.

Das immaterielle Kulturerbe in Nordrhein-Westfalen. Bewerbungs- und Auswahlverfahren - Harnack, Maria (Heimatpflege in Westfalen)

Richtig schreiben. - Topalović, Elvira; Uhl, Benjamin (Deutsch lernen: Hören – Sprechen – Lesen – Schreiben.)

Lesen und schreiben lernen. - Topalović, Elvira (Deutsch lernen: Hören – Sprechen – Lesen – Schreiben.)

Sprachsensibler Mathematikunterricht in Hauptschulen. Sprache im Fach aus Sicht von Sprachfördercoaches, Lehrkräften und Lernenden in einem BiSS-Projekt. - Jörg, Jost; Topalović, Elvira; Uhl, Benjamin (Fachunterricht und Sprache in schulischen Lehr-/Lernprozessen.)

Schuld und Wahrheit in der sprachlichen Konstruktion von Hexen. Ein interdisziplinärer Zugang zu Kassibern und Protokollen. - Topalović, Elvira (Wissenstransfer – Interdisziplinäre Zugänge zur Vermittlung von Magie- und Zauberei-Imaginationen)

Gemeinsames Lernen im Sprachunterricht: Wie können Lernaufgaben sprachlich variiert werden? - Uhl, Benjamin; Topalović, Elvira (Inklusiver Unterricht in der Grundschule)

Texte zu Hexenverfolgungen des 17. Jahrhunderts im integrativen Unterricht. Ansätze für die Sekundarstufe in den Fächern Deutsch und Geschichte. - Blachut, Alisa; Topalović, Elvira (Deutsch im 17. Jahrhundert. Studien zu Sprachkontakt, Sprachvariation und Sprachwandel im Deutschen)

Mit Bildern sprechen (Modul 4) - Blachut, Alisa (Deutsch lernen: Sprechen – Zuhören – Lesen – Schreiben. DaM – DaZ – DaF)

Marx lesen im Informationszeitalter: Eine medien- und kommunikationswissenschaftliche Perspektive auf „Das Kapital Band 1“ - Fuchs, Christian

Marx and the political economy of the media. Studies in critical social sciences. Volume 79. Paperback

Information Technology and Sustainability in the Information Society - Fuchs, Christian (International Journal of Communication)

Fascism 2.0: Twitter Users’ Social Media Memories of Hitler on his 127th Birthday - Fuchs, Christian (Fascism: Journal of Comparative Fascist Studies)

The Information Economy and the Labor Theory of Value - Fuchs, Christian (International Journal of Political Economy)

Raymond Williams’ Communicative Materialism - Fuchs, Christian (European Journal of Cultural Studies)

Critical Social Theory and Sustainable Development: The Role of Class, Capitalism and Domination in a Dialectical Analysis of Un/Sustainability - Fuchs, Christian (Sustainable Development)

The Praxis School’s Marxist Humanism and Mihailo Marković’s Theory of Communication - Fuchs, Christian (Critique)

Sustainability and Community Networks - Fuchs, Christian (Telematics and Informatics)

信息时代重读马克思的《资本论》[J] - Fuchs, Christian (国外理论动 (Foreign Theoretical Trends) 2017 (12))

Herbert Marcuse and the Dialectics of Social Media - Fuchs, Christian (The Great Refusal: Herbert Marcuse and Contemporary Social Movements)

Facebook - Fuchs, Christian (Global Media Giants)

Preface: Horst Holzer’s Marxist Theory of Communication [Preface to Christian Fuchs’ translation of Horst Holzer’s article “The Forgotten Marxist Theory of Communication & Society“] - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

The Relevance of Franz L. Neumann’s Critical Theory in 2017: “Anxiety and Politics“ in the New Age of Authoritarian Capitalism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Günther Anders’ Undiscovered Critical Theory of Technology in the Age of Big Data Capitalism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

The Financialisation of Digital Capitalism in China - Fuchs, Christian; Xia, Bingqing (Westminster Advanced Studies Research Paper)

Die Kritik der Politischen Ökonomie der Medien/Kommunikation: ein hochaktueller Ansatz - Fuchs, Christian (Publizistik)

YouTube’da reklamlar faşizmle buluşunca: Yeni Google skandalı bize büyük veri kapitalizmi hakkında ne söylüyor? - Fuchs, Christian (Sendika.org)

When Ads Meet Fascism On YouTube: What The Recent Google-Scandal Tells Us About Big Data Capitalism (Long version) - Fuchs, Christian (Medium.com)

When Ads Meet Fascism On YouTube: What The Recent Google-Scandal Tells Us About Big Data Capitalism (Short version) - Fuchs, Christian (Huffington Post)

社群媒體批刊理論 - Fuchs, Christian

Zero-Hour Contracts are Turning University Lecturers Off the Jo - Allmer, Thomas (The Conversation)

"Niemand kennt die Jugendlichen besser als wir". Zur Differenz zwischen Selbst- und Fremdwahrnehmung junger Erwachsener in beruflichen Integrationsmaßnahmen. - Niemeyer-Jensen, Beatrix; Zick, Sebastian; Dehmel, Lukas (Forum Erwachsenenbildung)

"Ihr seid irgendwie mit involviert". Das Verhältnis von Wissenschaft und Praxis in der Berufsvorbereitung aus Perspektive der Praxis - Zick, Sebastian; Dehmel, Lukas (bwp@ - Berufs- und Wirtschaftspädagogik online)

Integrating volunteers: the operationalization of resilience in German civil security research - Hälterlein, Jens; Madsen, L; Schuchardt, A; Peperhove, R; Gerhold, L (Urban Disaster Resilience and Security – Novel Approaches for Dealing with Risks in Societies)

Habermas und der Neoliberalismus. Zum Diskurs der Konsumkritik und seinen Effekten - Hälterlein, Jens (kultuRRevolution, nr. 72)

Internet Surveillance After Snowden: A Critical Empirical Study of Computer Experts’ Attitudes On Commercial And State Surveillance of the Internet and Social Media Post-Edward Snowden - Fuchs, Christian; Trottier, Daniel (Journal of Information, Communication & Ethics in Society)

From Digital Positivism and Administrative Big Data Analytics Towards Critical Digital and Social Media Research! - Fuchs, Christian (European Journal of Communication)

Marx’s Capital in the Information Age - Fuchs, Christian (Capital & Class)

卡尔·马克思与当代媒介和文化研究 [J] - Fuchs, Christian (国外理论动态 (Foreign Theoretical Trends) 2017 (6))

Hacia un estudio Marxiano del Internet. Translated by Adrián Montero Morera - Fuchs, Christian (Revista de Ciencias Sociales Universidad de la Universidad de Costa Rica)

Fake News Is Not Just The Word Of The Year, But A Danger To Democracy That Can Only Be Overcome By Adequate Legal And Media Reforms - Fuchs, Christian (Huffington Post)

What is to Be Done? The Role of the New and the Old in Media Theory – The Moment for Critical Digital and Social Media Studies - Fuchs, Christian (Westminster Papers in Communication and Culture)

Donald Trump: A Critical Theory-Perspective on Authoritarian Capitalism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

How the Frankfurt School Helps Us to Understand Donald Trump’s Twitter Populism - Fuchs, Christian (The Huffington Post)

Donald Trumps Schlachtfeld: Der neue Präsident nützt Twitter als populistische Waffe. Warum ist er damit so erfolgreich? - Fuchs, Christian (Der Falter 5/2017)

Towards the Public Service Internet as Alternative to the Commercial Internet - Fuchs, Christian (ORF Texte No. 20 – Öffentlich-Rechtliche Qualität im Diskurs)

Written Evidence Submitted to the House of Commons-Digital, Culture, Media and Sport Select Committee’s Inquiry on Fake News. Published on November 28, 2017 - Fuchs, Christian

Marx in the age of digital capitalism. Studies in critical social sciences, Volume 80. Paperback

Social Media. A Critical Introduction. Second edition - Fuchs, Christian

Facts: Handle with care - Matzner, Tobias (Medium.com)

PostCapitalism: A Guide to Our Future - Allmer, Thomas (The Journal of Contemporary Community Education Practice Theory)

Privatheit in öffentlichen WLANs - Eisele, Daniel; Grigorjew, Olga; Karaboga, Murat; Matzner, Tobias; Morlok, Tina; Nebel, Maxi; Ochs, Carsten; Robrahn, Rasmus; Rzepka, Christine; Simo Fhom, Hervais (Whitepaper des Forums Privatheit und Selbstbestimmung in der digitalen Welt)

Notification services and our hidden dependence on proprietary network infrastructures - Matzner, Tobias (Medium.com)

Sorting Things Out Ethically – Privacy as a Research Issue Beyond the Individual - Matzner, Tobias; Ochs, Carsten (Internet Research Ethics for the Social Age: New Cases and Challenges)

Is there a Right to Offline Alternatives in a Digital World? - Karaboga, Murat; Matzner, Tobias; Obersteller, Hannah; Ochs, Cartsten (Data Protection and Privacy: (In)visibilities and Infrastructures)

Opening Black Boxes Is Not Enough – Data-based Surveillance In Discipline and Punish And Today - Matzner, Tobias (Foucault Studies 23 (2017))

Seán Allan, Sebastian Heiduschke (Hg.): Re-Imaginig DEFA. East German Cinema in its National and Transnational Contexts. New York: Berghahn, 2016 - Ahrens, Stephan (In: Filmblatt Nr 63)

Neugier auf den Kanon [Besprechung von Thomas Christen (Hg.): Vom Neorealismus zu den Neuen Wellen. Filmische Erneuerungsbewegungen 1945-1968. Einführung in die Filmgeschichte Band 2. Marburg, Schüren, 2016] - Ahrens, Stephan (Filmbulletin Nr. 4)

Kontra wird nicht gegeben [Besprechung von Der neue Mensch. Aufbruch und Alltag im Revolutionären Russland. Edition suhrkamp, Absolut medien]. - Ahrens, Stephan (Film-Dienst Nr. 9)

Anbruch eines neuen Kinos? [Besprechung von Astrid Deuber-Mankowsky: Queeres Post-Cinema. Berlin, August, 2017] - Ahrens, Stephan (Filmbulletin Nr. 6)

Alle Grenzen sprengen. Über Heiner Carows Filme „Die Russen kommen“ und „Karriere“ - Ahrens, Stephan (Film-Dienst, Nr. 11)

„Zeig der Welt nicht dein Herz …“ Ein Loblied auf die Schauspielerin Pola Negri - Ahrens, Stephan (Film-Dienst, Nr. 17)

Selbst/Begegnungen im Film. Erinnerungen an den deutschen Filmkomponisten Hans Posegga - Ahrens, Stephan (Film-Dienst Nr. 4)

Unter anderem Maurice Tourneur - Ahrens, Stephan (Filmbulletin Nr. 7)

Das nackte Überleben. Jörg Später begibt sich auf die Suche von Siegfried Kracauer - Ahrens, Stephan (Jüdische Allgemeine, Nr. 1)

Der Sog verborgener Bilder [über die Rekonstruktion und Restaurierung von Adamu Halilus Shaihu Umar] - Ahrens, Stephan (Film-Dienst Nr. 3)